2016
DOI: 10.1063/1.4940440
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting phase domains for memory applications

Abstract: In this work we study theoretically the properties of S-F/N-sIS type Josephson junctions in the frame of the quasiclassical Usadel formalism. The structure consists of two superconducting electrodes (S), a tunnel barrier (I), a combined normal metal/ferromagnet (N/F) interlayer and a thin superconducting film (s). We demonstrate the breakdown of a spatial uniformity of the superconducting order in the s-film and its decomposition into domains with a phase shift π . The effect is sensitive to the thickness of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
(45 reference statements)
0
30
0
2
Order By: Relevance
“…To conclude, we derived and analyzed numerically equations describing behavior of a Josephson junction in local inhomogeneous magnetic field. As discussed in the Introduction, such situation may have many different reasons and experimental realizations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27]. It was demonstrated that time-dependent local field provides an additional driving force, which may induce flux-flow type dynamics in long junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, we derived and analyzed numerically equations describing behavior of a Josephson junction in local inhomogeneous magnetic field. As discussed in the Introduction, such situation may have many different reasons and experimental realizations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27]. It was demonstrated that time-dependent local field provides an additional driving force, which may induce flux-flow type dynamics in long junctions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many experimental situations JJ's are subjected to a local, strongly inhomogeneous magnetic field. For example, it can originate from a self-induced flux in JJ's with a sign-reversal order parameter [7][8][9]; appear in JJ's containing ferromagnetic interlayers with spatially inhomogeneous thicknesses [10][11][12][13], nanoparticles or domain walls [14][15][16][17][18][19]; in JJ's with a local current injection [20,21]; can be induced by a nearby Abrikosov vortex [22][23][24][25], by a sharp tip of a Magnetic Force Microscope (MFM) [26,27], etc. Although such a situation has been considered previously, often this has been done without proper substantiation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can operate as autonomous and persistent phase batteries -one of key elements of quantum [1,[5][6][7][8][9][10][11][12][13][14] and digital Josephson electronics [2,3,15,16]. Such junctions can be also used for development of novel types of cryogenic memory [17][18][19][20][21][22]. The π-phase shift is most commonly needed, e.g., for bringing the flux-qubit to the degeneracy point [1,[5][6][7], for realization of complementary digital Josephson electronics [2,3,15,16] and for maximum distinction between 0 and 1 state in a memory cell [17].…”
Section: Introductionmentioning
confidence: 99%
“…В гибридных SFS-структурах это достигается путем изменения толщины ферромагнитно-го слоя [13] и/или при использовании комбинированного барьера, состоящего из участков нормального (N) металла и ферромагнетика [14]. Подобные системы с искусственно созданным чередованием 0 и π контактов обладают необычной (отличной от фраунгоферовой) зависимостью критического тока I c от внешнего магнитного поля H 0 [15,16] и допускают спонтанную генерацию вихрей с магнитным потоком, равным доле кванта магнитного потока 0 = π c/|e| на границах между 0 и π участками перехода [17,18].…”
Section: Introductionunclassified
“…Джозефсоновская разность фаз в основном состоянии 0−π перехода может принимать произвольное значение 0 < ϕ < π [19,20], что позволяет использовать такой ϕ-контакт в качестве источника заданного фазового сдвига (фазовой батареи) в контурах сверхпроводящих квантовых интерферометров [21]. Предложенный в [14] дизайн гибридной структуры с комбинированным F/N-барьером может оказаться перспективным для разработки на его основе сверхпроводящей ячейки памяти. Заметим, что при отсутствии структурных неоднородностей на FS-границе продольная слоям фазовая модуляция сверхпроводящего параметра порядка возможна из-за формирования неоднородного состояния Ларкина−Овчинникова−Фульде−Феррелла (ЛОФФ) [22,23].…”
Section: Introductionunclassified